(untitled) (World Bulletin of Management and Law, 2023)
The concepts of "equality" and "equality" are often used as equivalent terms in the legal literature. Some scholars believe that "subjective rights and responsibilities in the parental relationship merge together", parental rights are also parental responsibilities at the same time.